Tuberous Sclerosis Complex in a Family (Journal of Medicine, 2010)
Tuberous sclerosis, also known as tuberous sclerosis complex (TSC), is an autosomal dominant, multisystem, neurocutaneous disorder characterized by development of widespread hamartomatous lesions involving skin, brain, kidney, retina etc. Contrary to the popular belief, the disease has variable degree of expressivity and not all patients have the severe debilitating form. We report two cases of tuberous sclerosis complex in a family and then the literature is reviewed. Keywords: Tuberous sclerosis, neurocutaneous syndrome, hamartoma, phakomatosis DOI:10.3329/jom.v11i1.4284 J Medicine 2010: 11: 94-98